Non-randomized controlled prospective study on perioperative levels of stress and dysautonomia during dental implant surgery - Morino, Miyuki; Masaki, Chihiro; Seo, Yoshinori; Mukai, Chisato; Mukaibo, Taro; Kondo, Yusuke; Shiiba, Shunji; Nakamoto, Tetsuji; Hosokawa, Ryuji (Journal of prosthodontic research, 2014)
The purpose of this study was to compare pre- and postoperative autonomic activities and changes in salivary stress biomarkers between patients who received only local anesthesia and those who received local anesthesia together with intravenous sedation in dental implant surgery. A total of 21 patients were enrolled in this non-randomized controlled prospective study; 7 subjects underwent implant surgery under local anesthesia with intravenous sedation and 14 subjects underwent surgery under only local anesthesia. Stress was evaluated by measuring salivary levels of chromogranin A (CgA) and a spectral analysis of heart rate variability (HRV) at baseline (on a day other than the day of surgery), 1h preoperatively, and 1h postoperatively. HRV analysis yields low- (LF) and high-frequency (HF) components, the LF/HF ratio, and the component coefficient of variance (CCV[HF]), which provide indices of sympathetic and parasympathetic regulatory activity. CgA levels were significantly higher (p<0.05) at baseline in patients who received sedation than those who did not, but CgA levels did not differ prior to surgery. Also, the values of most parameters, including LF, HF, LF/HF (L/H), and CCV(HF), did not significantly differ between groups or among the three time points. Only ΔL/H and ΔCCV(HF) were significantly lower (p<0.05) at 1h preoperatively in patients who received sedation than those who received only local anesthesia. CgA levels were high in both groups immediately before surgery, and thus CgA values immediately before surgery may not be a reliable indicator of the need for intravenous sedation. Also, spectral analysis of HRV, especially ΔL/H and ΔCCV(HF), could be useful for assessing tension and anxiety.